HARMONISASI NILAI SYARIAH DAN PRAKTEK PERBANKAN MENUJU SISTEM YANG ADIL DAN TRANSPARAN - Hardianto S; Kurniati; Qadir Gassing (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2025)
This study analyzes the differences between conventional and Islamic banking systems in Indonesia in responding to the demands of modern society for justice and transparency. The results of the study indicate that public interest in Islamic banking has increased significantly, primarily because its profit-sharing system is more transparent and equitable compared to conventional bank interest, which is often complex and opaque. However, the study also reveals unfair practices that still occur in several conventional banks, such as hidden fees, confusing interest calculations, and discriminatory treatment of small customers. Through a quantitative approach using OJK data analysis and customer surveys, this study provides concrete solutions for banks to enhance justice and transparency, including product simplification, technology adoption, and internal policy reform. The research findings emphasize the importance of transforming the conventional banking system by adopting principles of honesty and openness, and the need to strengthen regulations to protect customers. In conclusion, the development of banking in Indonesia must be directed towards creating a more inclusive, fair, and transparent system to meet the needs of a modern society that is increasingly critical and financially literate.